The Future Internet: Future Internet Assembly 2013: Validated Results and New Horizons - Galis, Alex (Lecture Notes in Computer Science, 2013)
Computer Communication Networks; Information Systems Applications (incl.Internet); Management of Computing and Information Systems; Multimedia Information Systems; Information Storage and Retrieval; Computers and Society